2016
DOI: 10.5262/tndt.2016.1003.12
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol Protects Peritoneal Membrane Function in Encapsulating

Abstract: OBJECTIVE:The most lethal complication of peritoneal dialysis is encapsulating peritoneal sclerosis (EPS), which develops as a result of epithelio-mesenchymal transformation (EMT) and known fibrotic processes. Paricalcitol has previously been shown to inhibit both EMT and fibrosis. We investigated the effect of paricalcitol on EPS. MATERIAL and METHODS:Forty non-uremic albino Wistar rats divided into four groups of equal numbers. The first group was administered 2 mL saline intraperitoneally (IP) and the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Previous studies that performed thermogravimetric analysis of pre-processed perlites reported that 2-5% of the sample corresponded to the volatile content (Barker et al, 2006;Gül, 2016;Haery, 2017). In this study, 4.81%, 2.76% and 3.62% of the samples belonged to the volatile content for "h", "f", and "g" perlites, respectively.…”
Section: Tgasupporting
confidence: 50%
See 4 more Smart Citations
“…Previous studies that performed thermogravimetric analysis of pre-processed perlites reported that 2-5% of the sample corresponded to the volatile content (Barker et al, 2006;Gül, 2016;Haery, 2017). In this study, 4.81%, 2.76% and 3.62% of the samples belonged to the volatile content for "h", "f", and "g" perlites, respectively.…”
Section: Tgasupporting
confidence: 50%
“…In literature, this approach of optical microscopy to SEM analysis were also used (Palomar and Barluenga, 2018). Not-flake shaped perlites were observed in the pre-processed perlites f, g, and h. While particles with a spongy and cracky shaped perlites were reported in several studies (Kaufhold et al, 2014;Gül, 2016;Pavlík and Bisaha, 2018;Vyšvařil et al, 2020), in this study flake-shaped perlites were observed as pulverized expanded perlites a, b, c, d, e in geometry wise. After obtaining from mine, raw perlites were crushed to coarse, fine, and micronized form in second industrial facility where perlites keep their unexpanded form.…”
Section: Sem Observationsmentioning
confidence: 61%
See 3 more Smart Citations